Pain intensity among institutionalized elderly: a comparison between numerical scales and verbal descriptors - Lílian Varanda Pereira; Gilberto de Araújo Pereira; Louise Amália de Moura; Rayanne Rodrigues Fernandes (SciELO, 2015)
AbstractOBJECTIVECorrelating two unidimensional scales for measurement of self-reported pain intensity for elderly and identifying a preference for one of the scales.METHODA study conducted with 101 elderly people living in Nursing Home who reported any pain and reached ( 13 the scores on the Mini-Mental State Examination. A Numeric Rating Scale - (NRS) of 11 points and a Verbal Descriptor Scale (VDS) of five points were compared in three evaluations: overall, at rest and during movement.RESULTSWomen were more representative (61.4%) and the average age was 77.0±9.1 years. NRS was completed by 94.8% of the elderly while VDS by 100%. The association between the mean scores of NRS with the categories of VDS was significant, indicating convergent validity and a similar metric between the scales.CONCLUSIONPain measurements among institutionalized elderly can be made by NRS and VDS; however, the preferred scale for the elderly was the VDS, regardless of gender.